Lateral cephalometric diagnosis of asymmetry in Angle Class II subdivision compared to Class I and II - Aparecida Fernanda Meloti; Renata de Cássia Gonçalves; Ertty Silva; Lídia Parsekian Martins; Ary dos Santos-Pinto (Dental Press Editora, 2014)
INTRODUCTION: Lateral cephalometric radiographs are traditionally required for orthodontic treatment, yet rarely used to assess asymmetries. OBJECTIVE: The objective of the present study was to use lateral cephalometric radiographs to identify existing skeletal and dentoalveolar morphological alterations in Class II subdivision and to compare them with the existing morphology in Class I and II relationship. MATERIAL AND METHODS: Ninety initial lateral cephalometric radiographs of male and female Brazilian children aged between 12 to 15 years old were randomly and proportionally divided into three groups: Group 1 (Class I), Group 2 (Class II) and Group 3 (Class II subdivision). Analysis of lateral cephalometric radiographs included angular measurements, horizontal linear measurements and two indexes of asymmetry that were prepared for this study. RESULTS: In accordance with an Index of Dental Asymmetry (IDA), greater mandibular dental asymmetry was identified in Group 3. An Index of Mandibular Asymmetry (IMA) revealed less skeletal and dental mandibular asymmetry in Group 2, greater skeletal mandibular asymmetry in Group 1, and greater mandibular dental asymmetry in Group 3. CONCLUSION: Both IDA and IMA revealed greater mandibular dental asymmetry for Group 3 in comparison to Groups 1 and 2. These results are in accordance with those found by other diagnostic methods, showing that lateral cephalometric radiography is an acceptable method to identify existing skeletal and dentoalveolar morphological alterations in malocclusions.